Predicting the theory of mind precursors based on parenting styles and language skills in preschool children - Khanipour, Hamid; Nezafatbakhsh, Sara; Aghababaee, Nasser; Zand, Samira (Iranian Journal of Child Neurology, 2021)
Objective The aim of this study was to examine the association between language skills and parenting styles and three levels of theory of mind in Iranian preschool children. Materials & Methods The sample consisted of 98 preschool Iranian children (aged 5-6) from Karaj province, Iran. While theory of mind test and test of language development (Told-p: 4) were administrated with children, their mothers were asked to answer a parenting style questionnaire. Results Multivariate regression analysis showed a differential relationship between three levels of theory of mind, language skills and parenting styles. The results indicated that the theory of mind were predicted by most of the language skills and permissiveness parenting styles (P < 0. 01). False belief understanding was predicted only by morphological completion (p < 0.01). In addition, word articulation and authoritative parenting style were observed to predict ability to understand second order theory of mind (R2 = 28%). Conclusion The pattern of relationships between language and theory of mind in Persian language seems similar to previous studies in other languages. Language may play a dual role in theory of mind, such that; whereas for the first (basic) and the third (advanced) levels of theory of mind, language skills (such as relational vocabulary, morphological completion and word articulation) are among of those important prerequisites, for the medium level (false belief), syntactical skills are mostly important. In addition, it seems that authoritative parenting styles could facilitate the development of higher-order abilities related to theory of mind.